Análise dos parâmetros físico químicos do leite cru produzido por pequenos produtores da cidade de Mossoró e região - Gurgel, Danyelle (Universidade Federal Rural do Semi-Árido, 2017)
Milk is seen as an indispensable food for the human species since the first moments of life, since they are sources of nutrients such as carbohydrate, proteins, vitamins and minerals, that act in the process of nutrition and prevention of diseases of diverse age groups and physiological states. This work aimed to perform the physical-chemical characterization and evaluate the quality of milk received at Nutrivida Indústria de Laticínio LTDA by several producers in the city of Mossoró and region. The physical-chemical parameters analyzed were acidity, fat content, density, non-greasy solids, total solids and cryoscopic index. The results of the physico-chemical analyzes represented a considerable deviation from the values allowed by the legislation, mainly for the parameters of cryoscopic index and dry extract, approximately 62,5% and 81%, respectively, which are related to the management of milk and diet Animal, and also possible additions of water or other substance to milk, such as the urine of the animal. In addition, it was possible to relate the variation of the data collected with the rainy season in the milk producing regions, which may show that one of the consequences of the seasonal variations is the alteration in the feeding of the animal
Monografia
Keywords: Leite; Controle de qualidade; Análise físico-química; Milk; Quality control; Chemical physical analysis; ENGENHARIAS::ENGENHARIA QUIMICA